STRATEGIES IN TEACHING LITERATURE IN ENGLISH CLASSROOM - Maulizan ZA (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2014)
This essay discusses about some strategies in teaching literature in English classroom, focusing on teaching poems, prose, and plays. There are some strategies can be applied by the lecturer in teaching literature in English classroom. First of all, the lecturer should prepare the material presented to the students in the class. Secondly, lecturer can set some questions. Thirdly, always ask